Effect of simulation modules on Jordanian nursing student knowledge and confidence in performing critical care skills: A randomized controlled trial - Loai I. Tawalbeh (Elsevier, 2020)
Background: Simulation is known to have a significant effect as a teaching strategy in nursing education. However, no studies have been conducted to examine the effect of simulation on nursing students' knowledge and confidence in performing critical care skills in Jordan. Purpose: This study aimed to test the effect of simulation on university nursing students' knowledge and confidence in performing critical care skills for patients with cardiac, respiratory and neurological health problems. Method: A randomized controlled (pre-test-post-test) design was implemented. The experimental group (n = 38) attended 9 simulation scenarios, theoretical lectures and clinical training in hospital about cardiac, respiratory and neurological health problems, while the control group (n = 38) attended only the theoretical lectures and clinical training in hospital. Knowledge and confidence were measured using knowledge exam and self-confidence scale respectively. Results: A paired t-test indicated that mean knowledge and confidence regarding implementing critical care skills were significantly higher P < 0.001 in the post-test than that in the pre-test, in both the experimental and the control group. However, independent t test revealed that the students in the experimental group scored significantly higher P < 0.001 than control group in both knowledge and confidence regarding performing critical care skills. Conclusion: Theoretical and clinical training is valuable teaching strategies that help enhance knowledge and confidence in applying critical care skills. However, adding simulation has a more significant effect than theoretical and clinical training in improving nursing students' knowledge and confidence in performing critical care nursing skills. Author strongly recommended considering simulation as alternative effective educational approach for clinical training especially during COVID-pandemic.